Effectiveness of a brief motivational intervention in the management of risky alcohol use in primary care: ALCO-AP20 study protocol - Romero-Rodríguez, Esperanza; Pérula-Jiménez, Celia; Fernández-López, Sara; Cabello-Gracia, Gregorio; Fernández-García, José Ángel; Pérula-de Torres, Luis Ángel; Roldán-Villalobos, Ana; Leiva-Cepas, Fernando; Fernández-Márquez, Rodrigo; Parras-Rejano, Juan Manuel; , ALCO-AP-20 Collaborative Study Group (Frontiers in Medicine, 2023)
Background: Motivational interviewing (MI) could be a method for minimizing alcohol-related harm. The study aims to assess the effectiveness of a brief intervention, based on a MI, in patients with risky alcohol use attended in Primary Care (PC). Methods: A cluster-randomized, two-arm parallel, multicenter, open-label, controlled clinical trial. Fifty PC healthcare professionals from the province of Córdoba (Spain) will be randomized to one of the two study groups: 1) Experimental Group (EG): MI-based approach; 2) Control Group (CG): Usual care based on health advice. EG intervention: Professionals will receive a training program focused on MI, consisting of a training workshop and the use of pre- and post-workshop questionnaires to measure knowledge and skills acquired, as well as the degree of empathy, with a videotape of the health professionals with standardized patients, before and after the workshop, and subsequent training feedback. CG intervention: Workshop on the management of risky alcohol use based on health advice; participants will also complete the pre- and post-workshop questionnaires and be videotaped. Study population: Patients ≥14 years old with risky alcohol consumption (28 Standard Drink Units-SDU-/week in men and 17 SDU/week in women) or excessive alcohol use (≥6 SDU in men or ≥4 SDU in women, in less than 2 hours). It would be necessary to include 110 subjects/group to find a difference of 20% between the percentage of patients in abstinence between EG (37%) and CG (20%), alpha error of 5%, and statistical power of 80%. Assuming a loss rate of 5% and the cluster design effect, the number of subjects to be recruited is estimated at 197/group. The follow-up period will be 12 months. The primary outcome variables will be the self-reported alcohol use level and the Alcohol Use Disorders Identification Test (AUDIT) questionnaire score. Discussion: The study aims to demonstrate the effectiveness of the motivational approach in the comprehensive treatment of the patient with risky alcohol use, improving the empathy of the healthcare professionals and strengthening the healthcare professional-patient relationship to achieve the behavioral change of the patients with this problem in primary care consultations.